Symfonia wielkiego miasta. O wizerunku Nowego Jorku w "Manhattanie" Woody’ego Allena - Karkiewicz, Magdalena (Załącznik Kulturoznawczy, 2014)
One of the major objective of this essay is to show that Woody Allen’s Manhattan (1979) is a renewal of an old film genre called the city symphony. In this movie, the director outlined a suggestive portrait of his beloved New York City. After Annie Hall (1977), Manhattan is the second most complete expression of the specificity of Allen’s style, which consists of comic and tragic elements. Another object of this essay is to demonstrate that while creating the image of the metropolis the director particularly exploits the tools of film expression. Audiovisual layer of Allen’s work allows to juxtapose Manhattan with the city symphony (genre which came into being in the twenties as an innovative combination of documentary and avant-garde forms). The similarity between Manhattan and the original city symphonies is visible at the very beginning of the film, because of black and white, kaleidoscopic shots of metropolis as well as the backing sound (Rhapsody in Blue by George Gershwin). Allen’s picture is not only a sophisticated portrait of New York, but also the critical study of the society.